(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
You have to be able to out-compete your opponents in order to win in this jungle-likecompetition. There are indications that major corporations have absorbed smaller rivals. The Bank ofRajasthan Ltd. and ICICI Bank Ltd. merger served as the catalyst for this analysis of banking mergers.With a focus on the Indian Banking Industry, the purpose of this research is to investigate why bankscombine and acquire one another. Samples of 17 post-liberalization bank mergers are used for thispurpose. The number of branches, geographic reach, and synergies from a merger are all taken intoaccount in this analysis. Researchers and scholars in the fields of Human Resources Management andOrganizational Behaviour will find this article particularly interesting. A new perspective on mergers andacquisitions may be found in this paper, which sets the stage for future research.